面向知识经济时代的区域经济发展与人才资源开发利用 = Regional economic development and human resource management in new era - 刘家恒 Liu, Jia Heng (2008)
This dissertation carried out a relative in-depth research into how to development and utilize regional talent resources so as to facilitate the development of regional economy at the knowledge-based economy stage.